Model Pembelajaran NURS dalam Keterampilan Menulis Bahasa Jerman - Nurul Magfirah; Syamsu Rijal (Phonologie : Journal of Language and Literature, 2023)
Abstract. This research is a classroom action research which consists of two cycles. The purpose of this study was to determine the planning, process and results of applying the NURS learning model in the German language writing skills of class XI IPS 2 SMA Kartika XX-I Makassar. The data in this study consists of two types, namely: quantitative data and qualitative data. Qualitative data was obtained through observation and quantitative data obtained through the results of the writing skills test cycle I and cycle II. The results of the data analysis showed that the value of writing skills obtained by students in the first cycle was 77.94% while in the second cycle it was 85.27%. These results indicate that the application of the NURS learning model can improve the German writing skills of class XI IPS 2 SMA Kartika XX-I MakassarKeyword: Classroom Action Research, Writing Skills, NURS Learning Model